Pelatihan Pembuatan Sabun dari Minyak Jelantah Kegiatan P5 SMA Negeri di Bontang - Sobah, Saripah; Fitria, Fitria; Ratnawati, Ratnawati (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
Cooking oil has been used repeatedly, also known as used cooking oil. Used cooking oil or used oil is usually disposed of carelessly so that it becomes waste in the surrounding environment. This community service activity aims to educate the people of Bontang City about the dangers of using cooking oil. The participants of this activity are the people of Bontang City, especially high school / vocational / MA students. So that the results of community service, especially for students in Bontang City, can improve their abilities and bridge in educating the public about the dangers and utilization of used cooking oil waste. This activity consists of discussion, demonstration, and hands-on practice. The method in this community service is practice and demonstration to provide skills to participants in determining the right formula for making soap from used cooking oil. After this activity, it is hoped that high school/ vocational / MA students in Bontang City will be more aware of the dangers of using used cooking oil and can utilize used cooking oil waste in products that have useful value.